Respuesta :
Simplifying
7n + 8 = 6n + 4
Reorder the terms:
8 + 7n = 6n + 4
Reorder the terms:
8 + 7n = 4 + 6n
Solving
8 + 7n = 4 + 6n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation.
8 + 7n + -6n = 4 + 6n + -6n
Combine like terms:
7n + -6n = 1n 8 + 1n = 4 + 6n + -6n
Combine like terms:
6n + -6n = 0 8 + 1n = 4 + 0 8 + 1n = 4
Add '-8' to each side of the equation.
8 + -8 + 1n = 4 + -8
Combine like terms:
8 + -8 = 0 0 + 1n = 4 + -8 1n = 4 + -8
Combine like terms:
4 + -8 = -4 1n = -4
Divide each side by '1'.
n = -4
Simplifying
n = -4
7n + 8 = 6n + 4
Reorder the terms:
8 + 7n = 6n + 4
Reorder the terms:
8 + 7n = 4 + 6n
Solving
8 + 7n = 4 + 6n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation.
8 + 7n + -6n = 4 + 6n + -6n
Combine like terms:
7n + -6n = 1n 8 + 1n = 4 + 6n + -6n
Combine like terms:
6n + -6n = 0 8 + 1n = 4 + 0 8 + 1n = 4
Add '-8' to each side of the equation.
8 + -8 + 1n = 4 + -8
Combine like terms:
8 + -8 = 0 0 + 1n = 4 + -8 1n = 4 + -8
Combine like terms:
4 + -8 = -4 1n = -4
Divide each side by '1'.
n = -4
Simplifying
n = -4